Counter-hegemonic housing constructs for sustainable urbanism and urban resilience in the 21st century - Viriato, Marcos Felipe Alves da Silva; Pina, Silvia Aparecida Mikami Goncalves; Monteiro, Evandro Ziggiatti (Revista Nacional de Gerenciamento de Cidades, 2023)
In the face of the multiple environmental and social crises largely caused by the predatory behavior of human beings in their habitat, the main challenge that the human species must deal with is to build and nurture sustainable human communities so that their ways of inhabiting do not interfere with nature’s inherent ability to sustain life. This study aimed to elucidate counter-hegemonic contemporary housing constructs experienced in Intentional Communities (IC) that demonstrate ecological awareness in their ways of inhabiting. For this purpose, three case studies were selected that present international relevance in their ways of life by proposing ways of inhabiting that are alternative to mainstream society and configure different scenarios of project implementation and scale, such as Findhorn in Scotland, Auroville in India, and Christie Walk in Australia. The discussion sought to highlight similarities and differences in the ways of inhabiting experienced in each IC analyzed, besides proposing a correlation with ecological principles to emphasize the potential of such constructs for the resilience and sustainability of contemporary urban habitat. The results of this paper contribute to studies that propose a new epistemological approach to architecture from a systemic perspective, especially to studies dedicated to IC settlements whose underlying intention is to promote the equilibrium of the human in his habitat.